How bilingual are Malaysian undergraduates? A snapshot of the different bilingual categories in Malaysia - Fatin Nadiah Mahmud,; Khazriyati Salehuddin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Almost all literate Malaysians are able to communicate in at least two different languages. Hence, ideally, conducting research involving bilinguals should not be a problem mainly because Malaysia can be regarded as a country with an abundant supply of participants for bilingual studies. However, in reality, conducting research on bilinguals in Malaysia, particularly those that regard bilinguals as a variable, is indeed a challenge; bilingualism at individual levels varies depending on, among others, the frequency and amount of input, interaction opportunities, and the perceived need for certain languages. To understand the multifaceted nature of bilingual individuals in Malaysia, an online survey was conducted on 234 Malay-English bilingual undergraduates (205 females and 29 males) from a research university in Malaysia to investigate their language profile from various aspects of bilingual experiences. Results demonstrate that although the respondents can be categorised as Simultaneous Early Bilinguals, Sequential Early Bilinguals, and Late Bilinguals, these Age of Acquisition-based categorisation cannot determine whether they are Dominant (unbalanced) Bilinguals, Balanced Bilinguals, Passive Bilinguals, or Active (Productive) Bilinguals. This suggests that, although Malay is the National Language of Malaysia and English is its Official Second Language, when conducting research on bilingual individuals in Malaysia, researchers must not consider the bilinguals as homogeneous; instead, the bilinguals’ language profile should be investigated so as to ensure that the right conclusions will be made in their studies.